Partnership construction and value co-creation to address voids in rice production: the case of rice value chains in Uganda - Hilary, R.S.; Kibwika, P.; Sseguya, H. (Informa UK Limited, 2017)
Since the establishment of One Stop Center Farmer Associations (OSCAs) in Uganda 13 years ago, no documentation of the work done had been carried out. This study was conducted on the partnership and value co-creation initiatives implemented by two OSCAs in the rice value chain in Luwero and Bugiri districts, Uganda. The methodology used involved use of semi structured interviews and check lists for focus group discussions as well as key informant interviews. Eight focus group interviews were conducted, with an average attendance of six members per group (48 members) in Bugiri and 48 members in Luwero district. Interviews were also conducted for 44 key informants. A total of 140 respondents were interviewed both in the focus group discussions and as key informants. The information was analyzed with NVIVO software. Findings indicate that partnership construction and value co-creation occurred in the OSCA value chains, but have not yet reached the ideal status, although they have advanced through the stages of development. There is an increased number of actors with vast interests interacting with the OSCAs for value co-creation. However, the cooperative co-creation of value along the chain requires a focus on achieving all actor value propositions as well as optimal outcomes for all. The study, therefore, recommends that in the process of constructing partnerships and co-creation, it is necessary to be aware of differences in each actor’s views, motivations, and ways of working. This will lead to complementing each other through realizing and accepting differences to make the partnerships work.